7-Aryl-7-deazapurine 3′-deoxyribonucleoside derivative as a novel lead for Chagas' disease therapy: in vitro and in vivo pharmacology. Issue 4 (17th November 2021) - Cardoso-Santos, Camila; Ferreira de Almeida Fiuza, Ludmila; França da Silva, Cristiane; Mazzeti, Ana Lia; Donola Girão, Roberson; Melo de Oliveira, Gabriel; da Gama Jaen Batista, Denise; Cruz Moreira, Otacilio; Lins da Silva Gomes, Natália; Maes, Louis; Caljon, Guy; Hulpia, Fabian; et al.
Abstract: Background: The protozoan Trypanosoma cruzi is auxotrophic for purines and causes Chagas' disease (CD), a neglected illness affecting >6 million people. Combining the 3-deoxyribofuranose part of cordycepin with the modified purine ring of a nucleoside 'hit' led to the discovery of 4-amino-5-(4-chlorophenyl)-N7-(3′-deoxy-β-d -ribofuranosyl)-pyrrolo[2, 3-d]pyrimidine (Cpd1 ), revealing promising anti- T. cruzi activity. Objectives: To further evaluate Cpd1   in vitro and in vivo to fully assess its therapeutic potential against CD, covering cell culture sterilization through washout assays, drug combination with benznidazole and long-term administration in T. cruzi -infected mice. Results: Although less susceptible to Cpd1 than amastigotes, trypomastigotes present an impaired capacity to successfully establish intracellular infection of cardiac cultures. Combination of benznidazole with Cpd1 indicated no interaction (additive effect) (FIC index = 0.72) while administration to mice at one-tenth of the optimal dose (2.5 mg/kg and 10 mg/kg for Cpd1 and benznidazole, respectively) suppressed parasitaemia but failed to avoid mortality. Long-term treatment (60 days) gave a rapid drop of the parasitaemia (>98% decline) and 100% mice survival but only 16% cure. In vitro washout experiments demonstrated that although parasite release into the supernatant of infected cardiac cultures was reduced by >94%, parasite recrudescence did occur after treatment. Conclusions: Parasite recrudescence did occur after treatment corroborating the hypothesis of therapeutic failure due to subpopulations of dormant forms and/or genetic factors in persister parasites involved in natural drug resistance.